ISLAMIC LAW EPISTEMOLOGY THOUGHT OF PERSPECTIVE WAEL B. HALLAQ AND RELEVANCE TO ISLAMIC LAW IN INDONESIA - Moh Abd Rauf (Postgraduate Programme of UIN Kiai Haji Achmad Siddiq Jember, 2018)
Studies on the history of Islamic law in Indonesia can also serve as one of the foundations for Muslims in particular to determine the right strategy in the future to bring the nation and Islamic law closer. Although some theories of Islamic law development from the time of the Islamic empire to the time of reform (now) are still optimized. But in addition to the many advances in these developments are also still many obstacles that are difficult to overcome. One of the obstacles to many perceptions is that the implementation of Islamic law today is irrelevant to modern times. In enhancing the development of Islamic law in Indonesia there needs to be comprehensive reviews such as the history and epistemology of Islamic law. This article discusses the development of thought in the field of Islamic jurisprudence emphasizing on the aspect of Islamic legal epistemology which developed in Indonesia. The formulated concept by Wael B. Hallaq, he is a professor of Islamic law at Columbia University who concentrates on research in the field of Islamic law. In this study at least the writer proposes three summaries, first Prof. Hallaq's biography and and socio-historical life will be described with a historical and an analytical content approach to explain the epistemological reasoning concept of Islamic law. Second, to know the reasoning of the epistemology of Islamic Law in the Wael. B. Hallaq’s perspective. And the third, to know its relevance with developments with Islamic Law in Indonesia.